2017
DOI: 10.1002/hed.24885
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the incidence and factors predictive of outcome in patients with head and neck cancer with pulmonary nodules

Abstract: Patients presenting with head and neck cancer have a higher incidence of pulmonary nodules and a higher risk of malignancy. In contrast to the British Thoracic Society (BTS) guidelines, which use size to guide the need for serial scans, we would recommend follow-up imaging in all patients with head and neck cancer with nodules, irrespective of size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
2
4
1
Order By: Relevance
“…Our results are consistent with the previous report of Green et al 7 , who reported that in a cohort of 400 HNSCC patients pulmonary nodules were present in 58% of patients and the lung malignancy rate equalled 6%. However, the aforementioned study included patients regardless of their age or smoking history and a Supraglottic T1 N0 56 2010 2017 7 2 77 w M Supraglottic T2 N0 100 2008 2012 4 3 71 o M Glottic T2 N0 30 2003 2015 12 4 76 w M Glottic T2 N0 150 2007 2015 8 5 83 w M Supraglottic T3 N0 50 2012 2015 3 6 70 b F Supraglottic T4 N0 50 2012 2014 2 7 72 w F Supraglottic T2 N1 60 2005 2013 8 8 72 w M Supraglottic T3 N2 45 2013 2014 www.nature.com/scientificreports www.nature.com/scientificreports/ considerable percentage of included patients had oropharyngeal cancer, where smoking is not as pronounced a risk factor as in laryngeal cancer.…”
Section: Discussionsupporting
confidence: 94%
“…Our results are consistent with the previous report of Green et al 7 , who reported that in a cohort of 400 HNSCC patients pulmonary nodules were present in 58% of patients and the lung malignancy rate equalled 6%. However, the aforementioned study included patients regardless of their age or smoking history and a Supraglottic T1 N0 56 2010 2017 7 2 77 w M Supraglottic T2 N0 100 2008 2012 4 3 71 o M Glottic T2 N0 30 2003 2015 12 4 76 w M Glottic T2 N0 150 2007 2015 8 5 83 w M Supraglottic T3 N0 50 2012 2015 3 6 70 b F Supraglottic T4 N0 50 2012 2014 2 7 72 w F Supraglottic T2 N1 60 2005 2013 8 8 72 w M Supraglottic T3 N2 45 2013 2014 www.nature.com/scientificreports www.nature.com/scientificreports/ considerable percentage of included patients had oropharyngeal cancer, where smoking is not as pronounced a risk factor as in laryngeal cancer.…”
Section: Discussionsupporting
confidence: 94%
“…In our cohort, we were unable to identify any patient factors associated with the presence of a pulmonary nodule, despite previous reports that older patients are more likely to have nodules 3 . Although not found to be statistically significant in our cohort, previous smoking did appear to be associated with the presence of pulmonary nodules with 67.1% of smokers having pulmonary nodules and only 58.6% of those who had never smoked.…”
Section: Discussioncontrasting
confidence: 89%
“…The present study adds to the literature available on the significance of pulmonary nodules in patients with HNC. Previously, we have reported the prevalence of pulmonary nodules in patients with HNC to be as high as 58% 3 ; subsequently, similar results have been demonstrated in a group of patients with laryngeal cancer at 52%. The present study found that 61.8% of patients had at least one pulmonary nodule.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations